The effect of action observation combined with high-definition transcranial direct current stimulation on motor performance in healthy adults: A randomized controlled trial - Schwell, Gidon; Kozol, Zvi; Tarshansky, David; Einat, Moshe; Frenkel-Toledo, Silvi (Frontiers in Human Neuroscience, 2023)
Action observation (AO) can improve motor performance in humans, probably via the human mirror neuron system. In addition, there is some evidence that transcranial direct current stimulation (tDCS) can improve motor performance. However, it is yet to be determined whether AO combined with tDCS has an enhanced effect on motor performance. We investigated the effect of AO combined with high-definition tDCS (HD-tDCS) targeting the inferior parietal lobe (IPL) and inferior frontal gyrus (IFG), the main aggregates of the human mirror neuron system, on motor performance in healthy adults and compared the immediate vs. 24-h retention test effects (anodal electrodes were placed over these regions of interest). Sixty participants were randomly divided into three groups that received one of the following single-session interventions: (1) observation of a video clip that presented reaching movement sequences toward five lighted units + active tDCS stimulation (AO + active HD-tDCS group); (2) observation of a video clip that presented the same reaching movement sequences + sham HD-tDCS stimulation (AO + sham HD-tDCS group); and (3) observation of a video clip that presented neutral movie while receiving sham stimulation (NM + sham HD-tDCS group). Subjects’ reaching performance was tested before and immediately after each intervention and following 24 h. Subjects performed reaching movements toward units that were activated in the same order as the observed sequence during pretest, posttest, and retest. Occasionally, the sequence order was changed by beginning the sequence unexpectedly with a different activated unit. Outcome measures included mean Reaching Time and difference between the Reaching Time of the unexpected and expected reaching movements (Delta). In the posttest and retest, Reaching Time and Delta improved in the AO + sham HD-tDCS group compared to the NM + HD-sham tDCS group. In addition, at posttest, Delta improved in the AO + active HD-tDCS group compared to the NM + sham HD-tDCS group. It appears that combining a montage of active HD-tDCS, which targets the IPL and IFG, with AO interferes with the positive effects of AO alone on the performance of reaching movement sequences.